LEGO Star Wars character encyclopedia - Dolan, Hannah; Dowsett, Elizabeth; Last, Shari; Taylor, Victoria; DK Publishing, Inc. (London ; New York : DK Pub., 2011)
Meet the many minifigures of the LEGO Star Wars galaxy! From the different versions of Luke Skywalker and Han Solo to Greedo and the mouse droid, learn about each minifigure and the cool sets they star in, along with fascinating LEGO Star Wars facts.
Episode I -- Episode II -- Episode III -- Episode IV -- Episode V -- Episode VI -- Clone wars -- Expanded universe.
Includes index.
3-6
NC1180L
6.9
Keywords: Models and modelmaking -- Juvenile literature; Star Wars films -- Juvenile literature; LEGO toys -- Juvenile literature; Models and modelmaking; Star Wars films; Encyclopedias